Micromorphological, anatomical and molecular study of Hedera species (Araliaceae) in Iran - Amini, Elham; Nasrollahi, Fatemeh; Sattarian, Ali; Moradkhani, Mahboobeh Haji; Boozarpour, Sohrab; Habibi, Meisam (Acta Biologica Szegediensis, 2020)
Hedera, with 12 extant species, is a genus of evergreen climbers native to Europe, north Africa, and south Asia. In this study, the micromorphological, anatomical structure and molecular evidences of 11 populations from two species of Hedera (H. helix and H. pastuchovii) have been considered to evaluate the relationships in Hedera. In total, seven quantitative and qualitative characters of pollen were selected and measured. Based on this study, the anticlinal wall and surface sculpturing of seed support for separation of two species of Hedera. Micromorphology of epidermis illustrated two types of epidermal cells: puzzle-shaped and polygonal cells. Using nuclear (nrDNA ITS) marker, we reconstructed phylogenetic relationships within two species of Hedera. This data set was analyzed by phylogenetic methods including Bayesian inference, maximum likelihood, and maximum parsimony. In phylogenetic analyses, all members of two species formed a well-supported clade (PP = 1; ML/BS = 100/100) and divided into two major clades (A and B). Neighbor Net diagram demonstrated separation of the studied populations. The results showed that these taxa differ in taxonomically important micromorphological, anatomical and molecular characteristics and these data provide reliable evidence for separation of these two species.